Case report: A rare case of malignant solitary fibrous tumor within the joint cavity with review of the literature - Wang, Xiao-Jie; Zhou, Jia-Ping; Pan, Yao; Yu, Ri-Sheng (Frontiers in Oncology, 2024)
Solitary fibrous tumors (SFTs) are classified as fibroblastic/myofibroblastic tumors that originate from CD34-positive dendritic cells and usually occur in the pleura. In this paper, we describe a case of SFT within the joint cavity of the left knee. A 60-year-old man was admitted to hospital due to swelling in the left knee for the past 8 months without relevant trauma history. X-ray, computed tomography (CT), magnetic resonance imaging (MRI), and positron emission tomography–computed tomography (PET-CT) presented a large, ill-circumscribed, hypervascular, and highly enhanced mass with eccentric calcification and peripheral, intra-lesional vessels. Subsequently, the patient underwent surgical resection. Postoperative pathology confirmed the neoplastic cells to be positive for CD34, Bcl-2, and SATA6, therefore was finally diagnosed as malignant SFT. The patient developed bone metastases within 1 year after surgery. SFT in the joint cavity is rare, and it is difficult to make a preoperative diagnosis.